Introducing Azure SQL database : from deployment over migration to monitoring - Tender, Peter De (Apress, 2019)
"Discover everything you need to know to get started with Azure SQL Database, from deployment, to key features to migration and monitoring! This video introduces Azure SQL Database, a general-purpose relational database-as-a-service (DBaaS). Beginning from a base deployment of an Azure SQL instance, you will be introduced to the cloud-native features of the service and discover how to run highly available and production-ready database back-ends on Azure, without the underlying database server virtual machines. After the base deployment walkthrough, you'll learn how to replicate business-critical databases across multiple regions, as well as how to migrate a database from on-premises or VM-based scenarios to Azure SQL Database."--Resource description page